Colonic low‐grade endometrial stromal sarcoma and orthotopic endometrial stromal tumor with limited infiltration sharing the JAZF1‐SUZ12 gene fusion. (April 2014) - Tokinaga, Aya; Furuya, Mitsuko; Niino, Hitoshi; Udaka, Naoko; Asai‐Sato, Mikiko; Sekido, Hitoshi; Miyagi, Etsuko
<x xml:space="preserve">Abstract</x> Endometrial stromal tumors (ESTs) are composed of cells resembling endometrial stroma, and are divided into benign and malignant types based on morphology. Endometrial stromal nodule (ESN) is a benign localized tumor, and endometrial stromal sarcoma (ESS) is an infiltrative and potentially metastatic neoplasm. A series of genetic aberrations contribute to pathological diagnosis of ESTs. At present, subsets of ESN and ESS‐low grade (ESS‐LG) are characterized as JAZF1‐SUZ12/JJAZ1 gene fusion. The ESTs that show higher grade atypia but lack nuclear pleomorphism include YWHAE‐FAM22 ESS. Here we report an unusual case of ESTs. Sudden colonic perforation occurred to the patient, and emergency surgery was performed. Pathological findings suggested metastatic ESS. Thorough medical examination of the genital organs detected a 1 cm‐sized well‐demarcated uterine tumor. Microscopically, the tumor lacked infiltrative features, conforming to the definition of ESN. Both lesions demonstrated identical cytology and shared JAZF1‐SUZ12 gene fusion. Endometriosis was not found in any areas of the resected organs, strongly suggesting that the uterine orthotopic tumor metastasized. The current case uncovered the problems of differential diagnosis between ESN and ESS‐LG. We demonstrate detailed pathological features of the two lesions, and discuss the possibility of orthotopic EST with limited infiltration to develop into ESS‐LG.